Do Intellectual Capital and Corporate Governance have Value Relevance to the Market Performance? Evidence from Indonesia - Nadhira Hardiana; Noorina Hartati; Pesi Suryani; Lasando Lumban Gaol; Lies Zulfiati; Dahlifah (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2023)
We examine whether intellectual capital and corporate governance have value relevance to market performance. Intellectual capital is measured by VAIC™ (Pulic, 1998). We use annual report data from companies listed on the Indonesia Stock Exchange (IDX) and Corporate Governance Perception Index (CGPI) data from the Indonesian Institute for Corporate Governance (IICG) in the period of 2015–2019. Preliminary findings suggest that intellectual capital does not have value relevance to market performance, but corporate governance does have value relevance to market performance. This paper contributes to stakeholders in making economic decisions.